SISTEM MONITORING SUHU, KELEMBABAN, DAN CAHAYA BUDIDAYA JAMUR TIRAM DI JAMUR MADANI UNGARAN - ilham sazaly (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Oyster mushroom cultivation requires controlled environmental conditions, especially temperature, humidity, and light intensity. Instability in these parameters can reduce productivity and mushroom quality. This research aims to design and implement an Internet of Things (IoT)-based environmental monitoring system to support real-time monitoring of oyster mushroom cultivation at Jamur Madani Ungaran. The system uses a DHT22 sensor to measure temperature and humidity, and an LDR sensor to measure light intensity, controlled by an ESP8266 microcontroller as the data processing unit. The collected data are transmitted and visualized on the Blynk IoT platform using graphs and indicators for easier monitoring. Additionally, the system provides notifications when environmental parameters exceed the ideal thresholds. The testing results show that the system operates properly, provides accurate and stable data, and improves monitoring efficiency. In conclusion, this monitoring system offers a practical solution to support enhanced oyster mushroom production quality through optimal environmental supervision.